Estimating the Effects of Private School Vouchers in Multidistrict Economies - Ferreyra, Maria Marta (American Economic Review, 2007)
This paper estimates a general equilibrium model of school quality and household residential and school choice for economies with multiple public school districts and private (religious and nonsectarian) schools. The estimates, obtained through full-solution methods, are used to simulate two large-scale private school voucher programs in the Chicago metropolitan area: universal vouchers and vouchers restricted to nonsectarian schools. In the simulations, both programs increase private school enrollment and affect household residential choice. Under nonsectarian vouchers, however, private school enrollment expands less than under universal vouchers, and religious school enrollment declines for large nonsectarian vouchers. Fewer households benefit from nonsectarian vouchers. (JEL H75, I21, I22)